Puerto Belgrano, the military port of Argentina - Viñuales, Graciela Maria (2014)
In the late nineteenth century, Argentina decided to construct a military port . The young officer Félix Dufourq and the Italian engineer Luigi Luiggi defined its location 700 km south of Buenos Aires (38º 53'' S, 62º 05'' W). Luiggi also designed the port facilities and the city where the marines and civilian personnel who will work on the site still live. It was a location like any ?company town?, but with the care a strategic defense point should have. The law creating the port was passed in November 1896. Shortly after that, began the construction of the port area, which was finished in 1908. Throughout the years were materializing new buildings, extending functions whose were adapted to the technical and strategic developments that appeared.